In Vitro And In Vivo Study On The Identification Of Compounds That Alleviate Aβ42 Associated Neurodegeneration - Tan, Florence Hui Ping (2020)
Alzheimer’s disease (AD) is the most common type of neurological disorder globally. Its mechanism includes the distinctive aggregation of extracellular senile plaques made up of amyloid-beta (Aβ) in the brain. Among the Aβ isomers secreted in the brain, Aβ42 is the most neurotoxic and aggressive. Regardless of the immense research on AD, the full pathogenesis of this disease remains unknown. The main aim of this study was to identify compounds that are able to alleviate Aβ42’s negative effects.